MASA PERADABAN DINASTI MAMLUK DI MESIR - Rafi'atun Najah Qomariah; Diva Maylana Surya; Dinda Novrika Fitria Yusup (Tarbawi, 2023)
The birth of the Mamluk dynasty in Egypt in the 13th century marked an important period in the history of the Middle East. This dynasty was born from a military slave system which then took over political power. The Mamluk lifestyle was manifested by great military power, a prosperous economy, and a rich cultural heritage. The Mamluk dynasty also had an influence on Islamic civilization, including in the fields of architecture, art, science, science, and others. But before giving its glor to Islamic civilization The Mamluk dynasty went through a very long and difficult process. The destruction of Baghdad by the Mongol army made the Mamluk dynasty the savior of Islamic civilization with the success of the Mamluk troops who were able to repel the threat of destruction from the Mongol troops which ultimately made Egypt, Iraq and the surrounding areas intact and safe. So that Islamic civilization can develop religious values. The end of the Mamluk dynasty’d rule came in the 16th century when they faced external pressure and internal upheaval, ending their dominance in the region. Based on the background above, the focus of this article is: (1) the birth of the Mamluk Dynasty. (2) lifestyke of the Mamluk Dyasty (3) the collaps of the Mamluk Dynasty. This article uses a qualitative method, namely by collecting information or darta from literature and journal analysis as a reference. The purpose of this article (1) to find out the history of the founding of th Mamlu dynasty? (2) what wasthe lifestyle of the Mamluk dynasty? (3) how did the reign of the Mamluk dynasty end? The fina step that the author obtains the results of the research and writes the results into a scientific work so that readers know the history of the founding of te Mamluk kingdom until the collapse of the dynasty. The Mamluk dynasty was a dynasty that was founded in the 13th century in Egypt and this dynasty had a fairly lon history which resulted in the enthusiasm of the Mamluk to eradicate the threat from the Mongols.